If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 16 = x Reorder the terms: 16 + 15x = x Solving 16 + 15x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 16 + 15x + -1x = x + -1x Combine like terms: 15x + -1x = 14x 16 + 14x = x + -1x Combine like terms: x + -1x = 0 16 + 14x = 0 Add '-16' to each side of the equation. 16 + -16 + 14x = 0 + -16 Combine like terms: 16 + -16 = 0 0 + 14x = 0 + -16 14x = 0 + -16 Combine like terms: 0 + -16 = -16 14x = -16 Divide each side by '14'. x = -1.142857143 Simplifying x = -1.142857143
| n*2-23=0 | | -l-19l-1-23-2= | | -19l-l-23-2= | | 5y^2-16+11=0 | | -4(-6)+y=29 | | -91=9t+8 | | 7x^3-x^2-112x+16=0 | | x+(x*.15)=27.6 | | 5(8c-1)-12=38c+5 | | .50(10x-2)=4 | | 34-52(12n-34)+235=32+101(35n-1) | | x^3+2x=110 | | 26a+26b= | | 15s^2+32s-7=0 | | 146-3x=33x+18 | | 11-9x=175-37x | | 0.0625x^2-0.125x=1 | | x^2-2x+1=8 | | 18x-(2x-8)=40 | | 37-3x=6x+27 | | 68-4x=8x-20 | | 7-8x=127-29x | | -10=-5(t-8) | | 7-8x=127-39x | | z^2-15=0 | | 3(x+7m+5)= | | 3x-12=4x-12 | | 50(x)=-0.4x^2+80x-1600 | | -21=7y | | 5(x+2)-7(x-1)=1 | | c+5=3 | | (8z-2)(8-z)=0 |